Phase change energy storage box
By using phase change energy storage tanks in industrial recycled water, waste heat is stored and transferred to domestic water, the problem of energy waste in industrial production is solved and efficient energy utilization and sustainable development is achieved.
Patent Information
- Application Number
- CN202411317707.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The recycled water produced in industrial production contains a large amount of waste heat, but the existing technology is difficult to effectively utilize, resulting in waste of energy and affecting the sustainable development of industrial production and enterprise costs.
Design a phase change energy storage box, using composite phase change materials and heat exchange tubes, to store and transfer the waste heat in recycled water through latent heat, and to heat domestic water, including the preparation of micron-scale graphite microsphere-based composite phase change materials and Use a back-type U-tube or a plate hollow tube for heat transfer.
It realizes efficient storage and reuse of waste heat of industrial recycled water, reduces energy waste, improves energy utilization, reduces costs for industrial production, and is conducive to the sustainable development of enterprises.
Smart Images

Figure CN119197164A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of energy storage, and in particular to a phase change energy storage box. Background Art
[0002] In industrial production, the treated industrial waste gas and wastewater (recycled water) contain a lot of heat. Since there is no mature technology to make good use of the heat, it leads to huge energy waste, which is not only not conducive to the sustainable development of industrial production, but also causes a certain waste of financial and material resources of enterprises. Summary of the invention
[0003] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and propose a phase change energy storage box to extract, store and transfer waste heat from industrial recycled water, and then use it as an energy source to heat domestic water, thereby achieving high energy utilization.
[0004] A phase-change energy storage box of the present invention comprises a box body, wherein the box body is filled with a composite phase-change material, a heat exchange tube is buried in the composite phase-change material, and the inlet and outlet of the heat exchange tube extend to the outside of the box body; The preparation method of the composite phase change material is as follows: S1, dispersing nano-graphite and nano-cellulose in deionized water and then ball-milling to obtain a nano-graphite-cellulose mixed solution; S2, using an electronic atomizer to spray the nano-graphite cellulose mixed solution into a container filled with liquid nitrogen, then sieving the microspheres in the container, and freeze-drying the microspheres to obtain micron-sized graphite microspheres; S3, immersing the micron-sized graphite microspheres in the molten phase change material for a period of time and then filtering the mixture with heat to obtain the composite phase change material.
[0005] Furthermore, the heat exchange tube is a U-tube or a plate-type hollow tube.
[0006] Furthermore, the box body includes a stainless steel box and a foam box arranged inside the stainless steel box, and an acrylic plate is adhered to the inner wall of the foam box.
[0007] Furthermore, a plurality of temperature sensors are arranged at intervals on the inner wall of the box.
[0008] Furthermore, the mass ratio of nano-graphite to nano-cellulose is 1-10:1.
[0009] Furthermore, the mass volume ratio of nanographite to deionized water is 1-10:100 g / ml.
[0010] Furthermore, the ball milling speed is 400-600 r / min and the time is 2-4 h.
[0011] Furthermore, the phase change material is paraffin.
[0012] Furthermore, the specific operation of step S3 is: firstly put the micron-sized graphite microspheres and the phase change material into a container and then evacuate the container in a vacuum drying oven, then react at 80°C for 2h to obtain a micron-sized graphite microsphere-based composite phase change material, and then perform heat filtration in an oven at 80°C.
[0013] Further, freeze drying was performed for 72 hours.
[0014] The present invention ball-mills and emulsifies the solution of nano-graphite and nano-cellulose to form an emulsion in the mixed solution, so that the sprayed droplets can be cooled in liquid nitrogen to form microspheres; the nozzle of the electronic atomizer is of micron level, ensuring that the sprayed droplets are also of micron level, and the finally obtained microspheres are also of micron level.
[0015] When preparing the composite phase change material, the material is first evacuated to exhaust the air in the microspheres so that the high-temperature molten paraffin liquid can flow smoothly into the pores of the microspheres. The microporous structure of the microspheres can bind PW through capillary force to prevent PW from leaking due to melting phase change.
[0016] In the present invention, the microspheres prepared by mixing nano-graphite and nano-cellulose, ball-milling and then spraying them out with an electronic atomizer can form a micro-aerogel porous structure, which can better absorb the phase change material, thereby improving the loading rate. In addition, because graphite is also used as the raw material of the microspheres, the heat storage capacity and thermal conductivity of the micron-scale graphite microsphere-based composite phase change material are greatly improved, and it still has a high phase change enthalpy value after multiple cycles.
[0017] The present invention utilizes the characteristics of micron-sized graphite microspheres and compounds them with phase change materials, which not only solves the problem of melting and leakage of phase change materials due to the phase change process, but also improves the thermal conductivity of the heat storage material, and can transfer heat from the heat exchange tube and the composite phase change material in a timely and efficient manner.
[0018] The present invention utilizes a composite phase change material with high energy storage performance and high thermal conductivity to store the waste heat in the recycled water in the material as latent heat through a heat exchange tube. Therefore, the energy in the wastewater can be centrally stored and transferred to a specific scene, and then the stored energy can be released to realize the reuse of waste heat from industrial recycled water. The use of the energy storage box reduces energy waste, thereby improving energy utilization, reducing costs for industrial production, and is conducive to the sustainable development of enterprises. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a real photo of the micron-sized graphite microspheres prepared in the present invention.
[0020] Figure 2This is a real photo of the micron-sized graphite microsphere-based composite phase change material prepared by the present invention.
[0021] Figure 3 It is the DSC chart of Example 1-5.
[0022] Figure 4a -e is the BET diagram of Example 1-5.
[0023] Figure 5 are scanning electron microscope images of Examples 1-5; wherein (a)-(b) are electron microscope images of Example 1, (c)-(d) are electron microscope images of Example 2, (e)-(f) are electron microscope images of Example 3, (g)-(h) are electron microscope images of Example 4, and (i)-(j) are electron microscope images of Example 5.
[0024] Figure 6 This is a schematic diagram of a circular U-tube.
[0025] Figure 7 Schematic diagram of a plate-type hollow tube.
[0026] Figure 8 , 9 This is a schematic diagram of the interior of the energy storage box.
[0027] Fig.10 It is a temperature-time curve diagram of heat storage in the U-tube heat exchanger heat storage tank at a 70°C hot water source flow rate of 500ml / min.
[0028] Fig.11 The temperature-time curve of the U-tube heat exchanger heat storage box releasing heat at a flow rate of 500 ml / min.
[0029] Fig.12 The temperature-time curve of the U-tube heat exchanger heat storage box releasing heat at a flow rate of 1000ml / min.
[0030] Fig.13 The figure is a temperature-time curve diagram of heat storage in the heat storage tank of the hollow plate heat exchanger at a flow rate of 500 ml / min of 70°C hot water source.
[0031] Fig.14 This is the temperature-time curve of the heat storage box of the hollow plate heat exchanger releasing heat at a flow rate of 500 ml / min. DETAILED DESCRIPTION
[0032] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0033] The present invention adopts the following technical scheme to prepare the composite phase change material, including the following process steps: (1) Preparation of mixed solution of micron-sized graphite microsphere precursor Add 30 g of nanocellulose aqueous solution with a solid content of 2% into a 100 ml beaker, then measure 30 mL of deionized water and add it to the beaker for mixing, add 0.6 g, 1.8 g, 3 g, 4.2 g and 5.4 g of nanographite respectively into the mixed solution, stir with a magnetic stirrer for 30 min, place the solution in a planetary ball mill for 3 h, the speed of the ball mill is 500 r / min, pour the obtained mixed solution into a 100 ml beaker to obtain a nanographite cellulose mixed solution.
[0034] (2) Preparation of micron-sized graphite microspheres The obtained 60 ml nano-graphite cellulose mixed solution was added to the purchased electronic atomizer for preparation, and then 2 L of liquid nitrogen was poured into the Dewar flask for standby use. The nano-graphite cellulose mixed solution was sprayed into the Dewar flask filled with liquid nitrogen using the electronic atomizer. The electronic atomizer was stopped after each 10 ml was sprayed, and the spraying operation was performed again after waiting for five minutes. After all the solutions were sprayed, the excess liquid nitrogen in the Dewar flask was poured back into the liquid nitrogen storage bottle after waiting for another five minutes. A sieve was placed between the Dewar flask and the liquid nitrogen storage bottle, and the prepared microspheres were poured onto the sieve, and then transferred to a beaker. After sealing with filter paper, the microspheres were dried in a freeze dryer for 72 hours to obtain micron-sized graphite microspheres, such as Figure 1 shown.
[0035] (3) Preparation of microsphere-based composite phase change materials Weigh 1g of micron-sized graphite microsphere powder and 3g of paraffin wax in a beaker; put the beaker into a vacuum drying oven, evacuate the vacuum, and react at 80°C for 2h to obtain a micron-sized graphite microsphere-based paraffin wax composite phase change material, and then perform heat filtration in an oven at 80°C to finally obtain a micron-sized graphite microsphere-based composite phase change material, such as Figure 2 shown.
[0036] Example 1 Weigh 0.6g of nano-graphite powder, 30g of 2wt.% cellulose solution and 30ml of deionized water into a 100ml beaker, stir the solution in the beaker on a magnetic stirrer for half an hour, put the mixed solution in the beaker into a ball mill and grind for 3h, then take out the mixed solution from the ball mill, use an electronic atomizer to spray 60ml of the solution six times, 10ml each time, into the liquid nitrogen of a Dewar flask, with an interval of five minutes each time, put the frozen microspheres into a vacuum freeze dryer and dry for 72 hours before taking out to obtain micron-sized graphite microspheres.
[0037] After compounding micron-sized graphite microspheres and excess paraffin wax and then performing heat filtration, the obtained composite phase change material has a melting enthalpy of 117.3 J / g, a solidification enthalpy of 113.9 J / g, and a thermal conductivity of 0.6235 W / (m·k). According to the BET test, the material has a specific surface area of 16.5332 m² / g, a pore volume of 0.318644 cm³ / g, and an average pore diameter of 28.8965 nm.
[0038] Example 2 1.8 g of nanographite powder, 30 g of 2 wt.% cellulose solution and 30 ml of deionized water were weighed, and the rest was the same as in Example 1.
[0039] The melting enthalpy of the obtained composite phase change material is 137.2 J / g, the solidification enthalpy is 132.5 J / g, and the thermal conductivity is 0.6772 W / (m·k). According to the BET test, the specific surface area of the material is 69.2373 m² / g, the pore volume is 0.668389 cm³ / g, and the average pore diameter is 35.3571 nm.
[0040] Example 3 3 g of nano-graphite powder, 30 g of 2 wt.% cellulose solution and 30 ml of deionized water were weighed into a 100 ml beaker. The other conditions were the same as those in Example 1.
[0041] The melting enthalpy of the obtained composite phase change material is 121.7 J / g, the solidification enthalpy is 116.2 J / g, and the thermal conductivity is 0.7325 W / (m·k). According to the BET test, the specific surface area of the material is 62.2777 m² / g, the pore volume is 0.533866 cm³ / g, and the average pore diameter is 31.8875 nm.
[0042] Example 4 4.2 g of nanographite powder, 30 g of 2 wt.% cellulose solution and 30 ml of deionized water were weighed into a 100 ml beaker. The other steps were the same as those in Example 1.
[0043] The melting enthalpy of the obtained composite phase change material is 127.9 J / g, the solidification enthalpy is 124.3 J / g, and the thermal conductivity is 0.8023 W / (m·k). According to the BET test, the specific surface area of the material is 58.9647 m² / g, the pore volume is 0.507495 cm³ / g, and the average pore diameter is 31.9188 nm.
[0044] Example 5 5.4 g of nanographite powder, 30 g of 2 wt.% cellulose solution and 30 ml of deionized water were weighed into a 100 ml beaker. The other steps were the same as those in Example 1.
[0045] The melting enthalpy of the obtained composite phase change material is 102.3 J / g, the solidification enthalpy is 91.2 J / g, and the thermal conductivity is 0.6323 W / (m·k). According to the BET test, the specific surface area of the material is 8.8841 m² / g, the pore volume is 0.149452 cm³ / g, and the average pore diameter is 25.7325 nm.
[0046] Comparative Example 1 Direct use of halloysite composite paraffin: Weigh 3 g of halloysite powder and compound it with paraffin wax, then filter it hot.
[0047] The melting enthalpy of the obtained composite phase change material is 72.2 J / g, the solidification enthalpy is -73.09 J / g, the thermal conductivity is 0.25 W / (m·k), and the loading rate is only 33.6%.
[0048] Comparative Example 2 The nanographite in the raw material is replaced with halloysite to prepare the composite phase change material: 3 g of halloysite powder, 30 g of 2 wt.% cellulose solution and 30 ml of deionized water were weighed into a 100 ml beaker. The other steps were the same as those in Example 1.
[0049] The melting enthalpy of the obtained composite phase change material is -147.6 J / g, the solidification enthalpy is 150.8 J / g, the loading rate is increased from 33.6% to 68%, and the thermal conductivity is 0.3266 W / (m·k).
[0050] Comparative Example 3 Directly use nano graphite to compound paraffin: Weigh 3 g of nanographite and mix it with excess paraffin wax, then perform hot filtration.
[0051] The melting enthalpy of the obtained composite phase change material is -77.53 J / g, the solidification enthalpy is 82.08 J / g, the thermal conductivity is 0.5022 W / (m·k), and the loading rate is only 38%.
[0052] Table 1 Enthalpy value comparison table
[0053] From the data in Table 1 and Figure 3 It can be seen that after the microspheres are prepared, the loading rate and thermal conductivity of the microsphere-based composite phase change material are greatly improved compared with the original composite phase change material. The heat storage performance of Example 2 is also the best among the five examples. Figure 4a-e and BET test data show that the specific surface area, pore volume and average pore size of Example 2 are the largest among the five examples, which can explain the highest adsorption rate of the phase change material in Example 2. From the above data, it can be seen that with the increase of the ratio of nanographite to cellulose, the thermal properties of the composite phase change material first increase and then decrease.
[0054] Production of energy storage box The present invention designs and manufactures two types of heat exchange tubes made of red copper, namely, a return-shaped U-tube and a plate-type hollow tube.
[0055] U-tube Figure 6 As shown, high thermal conductivity copper is used as the raw material and arranged in a matrix of 7 rows and 7 columns. The inner diameter of the tube is 4mm, the outer diameter is 6mm, the total length is 13.34m, and the total volume is 0.38dm 3 , heat exchange area 0.252m 2 .
[0056] Plate type hollow tube Figure 7 As shown, four 220mm*220mm*6mm rectangular plates are arranged in parallel at a spacing of 60mm and connected by a tube with an inner diameter of 4mm, an outer diameter of 6mm and a length of 60mm. The total volume is 1.23dm 3 , heat exchange area 0.413m 2 .
[0057] The present invention selects a foam box with an outer volume of 390mm*390mm*390mm and an inner volume of 330mm*330mm*330mm as the box body of the energy storage box, and sticks an acrylic plate on the inner wall of the foam box, placing the composite phase change material in direct contact with the foam box to cause corrosion, and then placing the foam box in a customized stainless steel box to prevent the foam box from being damaged during daily use.
[0058] like Figure 8 , 9 As shown, the heat exchange tube is then placed in the box, and the composite phase change material and temperature sensor are filled in. The temperature sensor uses Capeson's ultra-fine T-type thermocouple, which is placed in the box at the bottom, middle, top, front, back, left and right positions to observe in real time whether the temperature change of the composite phase change material is uniform during the charging and discharging process of the energy storage box.
[0059] Two energy storage boxes were made, both using micron-scale graphite microsphere-based composite phase change materials as heat storage materials. The first energy storage box uses a circular U-tube as a heat exchanger, while the second energy storage box uses a plate-type hollow tube as a heat exchanger.
[0060] A test system simulating the actual situation was built in the laboratory. Water was heated by an intelligent temperature-controlled heater to simulate industrial recycled water containing waste heat. The hot water source was input into the box through the port of the heat exchange tube extending out of the box through a peristaltic pump that can intelligently adjust the water flow rate. When the hot water flows through the box, the heat is transferred to the composite phase change material through the heat exchange tube and stored. The temperature sensor placed in the box can detect the temperature change of the composite phase change material at different positions inside the box in real time on the computer, and obtain the temperature-time curve.
[0061] Example 6 Investigate the effect of a flow rate of 500 ml / min on the heat storage and heat release performance of the circular U-tube energy storage box: The micron-scale graphite microsphere-based composite phase change material, the U-shaped tube and seven temperature sensors were placed in a foam box with an outer volume of 390 mm*390 mm*390 mm and an inner volume of 330 mm*330 mm*330 mm, with an acrylic plate on the inner wall, and compacted. The foam box was then placed in a customized stainless steel box. Both ends of the heat exchange tube extended out of the box as water inlets and outlets.
[0062] Fig.10 The heat storage tank of the U-tube heat exchanger is stored with 70℃ hot water source flow rate of 500ml / min. After charging for about 2h, the composite phase change material reaches the phase change temperature and begins to change phase, and the temperature change tends to be gentle; the phase change is completed in about 10h, and then the temperature rises to 65℃ in a sensible heat manner. This process shows that the heat storage tank can be stored with a hot water flow rate of 500ml / min in about 10h.
[0063] A peristaltic pump with intelligent water flow rate regulation is used to introduce room temperature water into the heat exchange tube at a flow rate of 500 ml / min. When the room temperature water flows through the box, it receives heat transfer from the composite phase change material through the heat exchange tube and is heated. Seven temperature sensors placed in the box are used to detect the temperature changes of the composite phase change material at different positions inside the box in real time on the computer, and a temperature-time curve is obtained, such as Fig.11 .
[0064] The composite phase change material drops to the phase change temperature after about 20 minutes, then enters the phase change process, completes the phase change in about 1.5 hours, and then cools to room temperature in a sensible heat manner. The black line represents the temperature change of the outflowing water, and the water temperature change has the same trend as the temperature change of the composite phase change material.
[0065] Example 7 Investigate the effect of flow rate of 1000 ml / min on the heat storage and heat release performance of the circular U-tube energy storage box: The micron-scale graphite microsphere-based composite phase change material, the circular U-tube and 7 temperature sensors are placed in a foam box with an outer volume of 390 mm*390 mm*390 mm and an inner volume of 330 mm*330 mm*330 mm and an acrylic plate adhered to the inner wall, and compacted. The foam box is then placed in a customized stainless steel box. Both ends of the heat exchange tube extend out of the box as water inlets and outlets. A peristaltic pump with intelligent water flow rate adjustment is used to introduce room temperature water into the heat exchange tube at a flow rate of 1000 ml / min. When the room temperature water flows through the box, it is heated by the heat transfer of the composite phase change material through the heat exchange tube. The 7 temperature sensors placed in the box are used to detect the temperature changes of the composite phase change material at different positions inside the box in real time on a computer, and the temperature-time curve is obtained, as shown in the figure. Fig.12 .
[0066] The composite phase change material drops to the phase change temperature after about 20 minutes, then enters the phase change process, completes the phase change in about 1.5 hours, and then drops to room temperature in a sensible heat manner. The black line represents the temperature change of the outflowing water, and the water temperature change has the same trend as the temperature change of the composite phase change material. However, the water flow rate in this example is faster than that in Example 6, and the cold water stays in the heat exchanger for a shorter time, and does not have time to receive more heat transfer, so the water temperature of the outflowing water is lower than that in Example 6.
[0067] Example 8 The self-heat storage and heat release performance of the plate-type hollow tube energy storage box at a flow rate of 500 ml / min was investigated: The micron-scale graphite microsphere-based composite phase change material, plate-type hollow tube and 7 temperature sensors were placed in a foam box with an outer volume of 390 mm*390 mm*390 mm and an inner volume of 330 mm*330 mm*330 mm, with an acrylic plate on the inner wall, and compacted. The foam box was then placed in a customized stainless steel box. Both ends of the heat exchange tube extended out of the box as water inlets and outlets.
[0068] A peristaltic pump with intelligent water flow rate regulation is used to introduce 70°C water into the heat exchange tube at a flow rate of 500 ml / min. When the hot water flows through the tank, the heat is transferred to the composite phase change material through the heat exchange tube to store heat in the thermal storage phase. Fig.13 The heat storage tank of the hollow plate heat exchanger is stored with 70℃ hot water at a flow rate of 500ml / min. After charging for about 0.5h, the composite phase change material reaches the phase change temperature and begins to change phase, and the temperature change tends to be gentle; the phase change is completed in about 1h40min, and then the temperature rises to about 65℃ in a sensible heat manner. This process shows that the heat storage tank can be stored with a hot water flow rate of 500ml / min in about 1h40min.
[0069] A peristaltic pump with intelligent water flow rate regulation is used to introduce room temperature water into the heat exchange tube at a flow rate of 500 ml / min. When the room temperature water flows through the box, it receives heat transfer from the composite phase change material through the heat exchange tube and is heated. Seven temperature sensors placed in the box are used to detect the temperature changes of the composite phase change material at different positions inside the box in real time on the computer, and a temperature-time curve is obtained, such as Fig.14 .
[0070] After about 40 minutes, the composite phase change material reaches the phase change temperature and begins to change phase, and the temperature change tends to be gentle; the phase change is completed in about 2h40min, and then the temperature drops to room temperature in a sensible heat manner. This process shows that the heat release of the heat storage tank can be completed in about 2h40min at a normal temperature water flow rate of 500ml / min.
[0071] For matters not mentioned above, the prior art applies.
[0072] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A phase change energy storage box, characterized in that: It comprises a box body, the box body is filled with a composite phase change material, a heat exchange tube is buried in the composite phase change material, and the inlet and outlet of the heat exchange tube extend to the outside of the box body; The preparation method of the composite phase change material is as follows: S1, dispersing nano-graphite and nano-cellulose in deionized water and then ball-milling to obtain a nano-graphite-cellulose mixed solution; S2, using an electronic atomizer to spray the nano-graphite cellulose mixed solution into a container filled with liquid nitrogen, then sieving the microspheres in the container, and freeze-drying the microspheres to obtain micron-sized graphite microspheres; S3, immersing the micron-sized graphite microspheres in the molten phase change material for a period of time and then filtering the mixture with heat to obtain the composite phase change material.
2. The phase change energy storage box according to claim 1, characterized in that: The heat exchange tube is a return-type U-tube or a plate-type hollow tube.
3. The phase change energy storage box according to claim 1, characterized in that: The box body comprises a stainless steel box and a foam box which is sleeved in the stainless steel box, and an acrylic plate is adhered to the inner wall of the foam box.
4. The phase change energy storage box according to claim 1, characterized in that: A plurality of temperature sensors are arranged at intervals on the inner wall of the box.
5. The phase change energy storage box according to claim 1, characterized in that: The mass ratio of nano-graphite to nano-cellulose is 1-10:
1.
6. The phase change energy storage box according to claim 1, characterized in that: The mass volume ratio of nanographite to deionized water is 1-10:100 g / ml.
7. The phase change energy storage box according to claim 1, characterized in that: The ball milling speed is 400-600 r / min and the time is 2-4 h.
8. The phase change energy storage box according to claim 1, characterized in that: The phase change material is paraffin.
9. The phase change energy storage box according to claim 1, characterized in that: The specific operation of step S3 is: firstly put the micron-sized graphite microspheres and the phase change material into a container and then evacuate the container in a vacuum drying oven, then react at 80°C for 2h to obtain the micron-sized graphite microsphere-based composite phase change material, and then perform heat filtration in an oven at 80°C.
10. The phase change energy storage box according to claim 1, characterized in that: Freeze-dry for 72 hours.
Citation Information
Patent Citations
Heat storage phase change composite material as well as preparation method and application
CN108084973A
Phase-change microsphere, multifunctional phase-change temperature-adjustment fiber, preparation method for phase-change microsphere and preparation method for multifunctional phase-change temperature-adjustment fiber
CN108977910A
Phase change heat storage material with microsphere structure and preparation method thereof
CN111849424A
Nitrogen-doped hollow-structure graphite microsphere, composite negative electrode material and preparation method thereof
CN113644243A
High-temperature multi-heat-exchange-tube compact type phase-change heat exchange device
CN114322623A
